A Consistent and Implicit Rhie–Chow Interpolation for Drag Forces in Coupled Multiphase Solvers - Lucian Hanimann; Luca Mangani; Marwan Darwish; Ernesto Casartelli; Damian M. Vogt (International Journal of Turbomachinery, Propulsion and Power, 2021)
The use of coupled algorithms for single fluid flow simulation has proven its superiority as opposed to segregated algorithms, especially in terms of robustness and performance. In this paper, the coupled approach is extended for the simulation of multi-fluid flows, using a collocated and pressure-based finite volume discretization technique with a Eulerian–Eulerian model. In this context a key ingredient in this method is extending the Rhie–Chow interpolation technique to account for the unique flow coupling that arises from inter-phase drag. The treatment of this inter-fluid coupling and the fashion in which it interacts with the velocity-pressure solution algorithm is presented in detail and its effect on robustness and accuracy is demonstrated using 2D dilute gas–solid flow test case. The results achieved with this technique show substantial improvement in accuracy and performance when compared to a leading commercial code for a transonic nozzle configuration.